Nanofiber cross-linked proton exchange membrane, preparation method and high-temperature proton exchange membrane fuel cell

Through the nano fiber prepared by mixed with electrostatic spinning in a proton exchange film and cross -linking, the problem of poor mechanical strength and poor proton conductivity of phosphate doped PBI proton exchange membranes, realizing the mechanical strength and proton of proton exchange membranes Significant improvement in the conductivity.

CN119340436APending Publication Date: 2025-01-21SHANGHAI INST OF SPACE POWER SOURCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411359307.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing phosphoric acid-doped PBI proton exchange membrane has poor mechanical strength and poor proton conductivity.

Method used

The nanofibers prepared by electrospinning are doped into the membrane matrix and cross-linked with the membrane matrix to form a rich network structure and improve the mechanical strength and proton conductivity of the proton exchange membrane.

Benefits of technology

The mechanical strength and proton conductivity of the proton exchange membrane are significantly improved, which meets the high-temperature working conditions of high-temperature proton exchange membrane fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340436A_ABST
    Figure CN119340436A_ABST
Patent Text Reader

Abstract

The invention discloses a nanofiber cross-linked proton exchange membrane, a preparation method and a high-temperature proton exchange membrane fuel cell. The preparation method comprises the following steps: step 1, preparing nanofibers: dissolving a first polybenzimidazole polymer in a first organic solvent to obtain an electrostatic spinning solution, and then preparing the nanofibers by adopting an electrostatic spinning process; step 2, preparing a membrane matrix solution: dissolving a second polybenzimidazole polymer in a second organic solvent to obtain the membrane matrix solution; 3, preparing a proton exchange membrane: adding nanofibers into the membrane matrix solution, performing ultrasonic dispersion, adding a cross-linking agent, and uniformly mixing to form proton exchange membrane slurry; and coating the proton exchange membrane slurry on a flat plate, and forming the proton exchange membrane at 100-160 DEG C. The nanofiber cross-linked proton exchange membrane is prepared by doping the nanofiber prepared by electrostatic spinning into the membrane matrix, and compared with an existing proton exchange membrane prepared only through the membrane matrix, the nanofiber cross-linked proton exchange membrane has the advantages that the nanofiber can be used as a mechanical support of the proton exchange membrane after being doped into the membrane matrix, and the overall mechanical strength of the proton exchange membrane is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and in particular to a nanofiber cross-linked proton exchange membrane, a preparation method and a high-temperature proton exchange membrane fuel cell. Background Art

[0002] High temperature proton exchange membrane fuel cells (HT-PEMFCs) are a type of proton exchange membrane fuel cells with an operating temperature range of 140 to 200°C. They have broad application prospects due to their strong resistance to CO poisoning and simple system structure.

[0003] The proton exchange membranes commonly used in HT-PEMFCs include: phosphoric acid doped polybenzimidazole (PBI) proton exchange membrane, polysulfone proton exchange membrane, polyetheretherketone proton exchange membrane, etc. Among them, phosphoric acid doped polybenzimidazole (PBI) proton exchange membrane is considered to be the most promising high-temperature proton exchange membrane due to its high physical and chemical stability under high temperature conditions. However, so far, phosphoric acid doped PBI proton exchange membrane still has two major problems: i) poor mechanical strength; ii) poor proton conductivity. Summary of the invention

[0004] The purpose of the invention is to solve the technical problems of poor mechanical strength and poor proton conductivity of the existing phosphoric acid-doped PBI proton exchange membrane.

[0005] In order to achieve the above object, the present invention provides a method for preparing a nanofiber cross-linked proton exchange membrane, comprising:

[0006] Step 1, preparation of nanofibers:

[0007] The first polybenzimidazole polymer is dissolved in a first organic solvent to obtain an electrospinning solution, and then the nanofibers are prepared by an electrospinning process; in the electrospinning solution, the concentration of the first polybenzimidazole polymer is 5wt% to 25wt%.

[0008] Step 2, preparing membrane matrix solution:

[0009] The second polybenzimidazole polymer is dissolved in a second organic solvent to obtain a membrane matrix solution; in the membrane matrix solution, the concentration of the second polybenzimidazole polymer is 5wt% to 8wt%.

[0010] Step 3, preparing the proton exchange membrane:

[0011] The nanofibers are added to the membrane matrix solution, and after ultrasonic dispersion, a cross-linking agent pyridine-3,5-diyldimethanol is added and mixed evenly to form a proton exchange membrane slurry; the proton exchange membrane slurry is coated on a flat plate, and heated to 100° C. to 160° C. to cross-link the first polybenzimidazole polymer and the second polybenzimidazole polymer to form a proton exchange membrane.

[0012] Optionally, after step 3, the step of doping with phosphoric acid is further included:

[0013] At 80° C. to 120° C., the nanofiber cross-linked proton exchange membrane is immersed in 65wt% to 85wt% phosphoric acid to allow phosphoric acid to be doped into the nanofiber cross-linked proton exchange membrane.

[0014] Optionally, the first polybenzimidazole polymer and the second polybenzimidazole polymer are independently selected from one or more of the following:

[0015]

[0016] Optionally, the first polybenzimidazole polymer and the second polybenzimidazole polymer are the same polybenzimidazole polymer.

[0017] Optionally, in step 1 and step 2, the weight ratio of the first polybenzimidazole polymer to the second polybenzimidazole polymer is 1:3 to 1:20.

[0018] Optionally, the first organic solvent and the second organic solvent are independently selected from one or more of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide or dimethyl sulfoxide.

[0019] Optionally, in step 1, the temperature at which the first polybenzimidazole polymer is dissolved in the first organic solvent is 75-85°C; in step 2, the temperature at which the second polybenzimidazole polymer is dissolved in the second organic solvent is 75-85°C; in step 3, the temperature at which the nanofibers are dispersed in the membrane matrix solution is 20-30°C.

[0020] Optionally, in step 1, the electrospinning voltage is 10 kV to 25 kV, the syringe advancement speed is 0.01 mm / min to 5 mm / min, the spinning distance is 5 cm to 25 cm, the temperature is 20° C. to 25° C., and the spinning time is 10 to 200 min.

[0021] The present invention also provides a nanofiber cross-linked proton exchange membrane prepared according to the above preparation method, and a high-temperature proton exchange membrane fuel cell comprising the nanofiber cross-linked proton exchange membrane, wherein the high-temperature proton exchange membrane fuel cell also includes: a graphite bipolar plate, a catalyst layer (carbon-supported platinum catalyst Pt / C), and a gas diffusion layer (carbon paper).

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) The proton exchange membrane provided by the present invention has excellent mechanical strength:

[0024] ① The present invention prepares a nanofiber cross-linked proton exchange membrane by doping nanofibers prepared by electrospinning into a membrane matrix. Compared with the existing proton exchange membrane made only by a membrane matrix, the nanofibers doped into the membrane matrix can serve as mechanical support for the proton exchange membrane, thereby improving the mechanical strength of the proton exchange membrane.

[0025] ② The present invention cross-links the first polybenzimidazole polymer (for forming nanofibers) with the second polybenzimidazole polymer (for forming a membrane matrix) to cross-link the nanofibers with the membrane matrix, thereby forming a rich network structure in the proton exchange membrane and further improving the mechanical strength of the proton exchange membrane.

[0026] The cross-linking principle of the first polybenzimidazole polymer and the second polybenzimidazole polymer is as follows:

[0027] The crosslinking agent used in the present invention is an aromatic compound containing pyridine or benzene ring, and the side chain of the pyridine or benzene ring contains chlorine or hydroxyl. Under the condition of 140-160°C, the pyridine or benzene ring removes the chlorine ion or hydroxyl in the side chain to form a pyridine residue or a benzene ring residue; the first polybenzimidazole polymer and the second polybenzimidazole polymer remove the hydrogen ion in the imidazole to form the first polybenzimidazole residue and the second polybenzimidazole residue; the pyridine residue or the benzene ring residue connects the first polybenzimidazole residue and the second polybenzimidazole residue, so that the first polybenzimidazole polymer and the second polybenzimidazole polymer are crosslinked and polymerized.

[0028] Taking pyridine-3,5-diyl dimethanol as the crosslinking agent, and the first polybenzimidazole polymer and the second polybenzimidazole polymer as OPBI as an example, the crosslinking reaction chemical equation is as follows:

[0029]

[0030] Taking 4,4-dichlorobiphenyl as the crosslinking agent, and OPBI as the first polybenzimidazole polymer and the second polybenzimidazole polymer, the crosslinking reaction chemical equation is as follows:

[0031]

[0032] (2) The proton exchange membrane provided by the present invention has excellent proton conductivity:

[0033] The present invention forms a rich network structure in the proton exchange membrane by cross-linking the first polybenzimidazole polymer and the second polybenzimidazole polymer. The network structure can serve as a proton transfer channel to increase the proton transfer rate in the proton exchange membrane, thereby increasing the proton conductivity of the proton exchange membrane.

[0034] (3) The proton exchange membrane provided by the present invention has excellent structural stability:

[0035] The first polybenzimidazole polymer and the second polybenzimidazole polymer used in the present invention can be the same material, so that the membrane matrix and the doped nanofibers have excellent compatibility, enhance the interface bonding between the membrane matrix and the nanofibers, and make the proton exchange membrane made by the present invention have excellent structural stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is the proton conductivity of the phosphoric acid-doped nanofiber cross-linked proton exchange membrane of Examples 1-4 of the present invention.

[0037] Figure 2 This is a mechanical strength curve diagram of the phosphoric acid-doped nanofiber cross-linked proton exchange membrane of Examples 1-4 of the present invention.

[0038] Figure 3 This is a current-voltage curve diagram of the phosphoric acid-doped nanofiber cross-linked proton exchange membrane in a single cell according to Examples 1-4 of the present invention. DETAILED DESCRIPTION

[0039] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0040] Based on the background technology, in order to solve the technical problems of poor mechanical strength and poor proton conductivity of existing proton exchange membranes, the present invention provides a method for preparing a nanofiber cross-linked proton exchange membrane, the method comprising the following steps:

[0041] Step 1, preparing nanofibers: dissolving a first polybenzimidazole polymer in a first organic solvent to obtain an electrospinning solution, and then using an electrospinning process to prepare nanofibers.

[0042] Wherein, in the electrospinning solution, the concentration of the first polybenzimidazole polymer is 5wt% to 25wt%. If the concentration of the first polybenzimidazole polymer is too low, the electrospinning solution is too dilute, and it is difficult to prepare a fibrous structure by electrospinning, but a droplet structure appears; if the concentration of the first polybenzimidazole polymer is too high, the electrospinning solution is too thick, which may clog the nozzle of the electrospinning equipment and make it difficult to prepare nanofibers.

[0043] Step 2, preparing a membrane matrix solution: dissolving a second polybenzimidazole polymer in a second organic solvent to obtain a membrane matrix solution.

[0044] Among them, in the above-mentioned membrane matrix solution, the concentration of the second polybenzimidazole polymer is 5wt% to 8wt%. If the concentration of the second polybenzimidazole polymer is too low, the subsequently formed proton exchange membrane slurry is too thin and cannot be formed on the flat plate; if the concentration of the second polybenzimidazole polymer is too high, the subsequently formed proton exchange membrane slurry is too thick and is not easy to spread on the flat plate.

[0045] Step 3, preparing a proton exchange membrane: adding the nanofibers to the membrane matrix solution, adding a crosslinking agent pyridine-3,5-diyldimethanol and mixing evenly after ultrasonic dispersion to form a proton exchange membrane slurry; coating the proton exchange membrane slurry on a flat plate, heating to 100° C. to 160° C., so that the first polybenzimidazole polymer and the second polybenzimidazole polymer are cross-linked to form a proton exchange membrane.

[0046] The temperature at which the nanofibers are dispersed in the membrane matrix solution is 20°C to 30°C at room temperature, and the time is 1 to 3 hours. Since the polybenzimidazole polymers dissolve very slowly at room temperature, usually requiring dozens of hours to completely dissolve, the nanofibers will only dissolve slightly in the membrane matrix solution in a short period of time at room temperature, and their fiber structure is basically retained. The nanofibers can still be used as mechanical support for the proton exchange membrane in the future to improve the mechanical strength of the proton exchange membrane.

[0047] The nanofibers prepared by the present invention are nano-scale fibers at a microscopic scale, and are not fibers at a macroscopic scale but aggregated into floccules. The nanofibers can be evenly distributed in the membrane matrix solution, and the proton exchange membrane slurry can be evenly coated on a flat plate.

[0048] In some embodiments, the first polybenzimidazole polymer and the second polybenzimidazole polymer are independently selected from one or more of the following:

[0049]

[0050] In some embodiments, the first polybenzimidazole polymer (used to form nanofibers) and the second polybenzimidazole polymer (used to form a membrane matrix) may be the same material or different materials. When the first polybenzimidazole polymer and the second polybenzimidazole polymer are the same material, the membrane matrix and the nanofibers doped therein have excellent compatibility, and the interface bonding between the membrane matrix and the nanofibers is enhanced, so that the proton exchange membrane prepared by the present invention has excellent structural stability.

[0051] The following is a description with reference to specific embodiments.

[0052] Example 1

[0053] This embodiment provides a nanofiber cross-linked proton exchange membrane, which is prepared by doping nanofibers prepared by electrospinning into a membrane matrix.

[0054] The mass ratio of the first polybenzimidazole polymer and the second polybenzimidazole polymer used in this embodiment is 1:5. The first polybenzimidazole polymer and the second polybenzimidazole polymer are both mPBI, and the structural formula is as follows:

[0055]

[0056] The first organic solvent and the second organic solvent used in this embodiment are both N,N-dimethylacetamide.

[0057] The preparation method of the proton exchange membrane in this embodiment is as follows:

[0058] (1) Preparation of electrospinning solution: mPBI powder was added to N,N-dimethylacetamide solvent and stirred at 80° C. for 12 h until completely dissolved to obtain an electrospinning solution with an mPBI concentration of 15 wt %.

[0059] (2) Preparation of nanofibers: The electrospinning solution was placed in an electrospinning propulsion device, and the electrospinning voltage was set to 10 kV, the syringe propulsion speed was set to 0.1 mm / min, the spinning distance was set to 5 cm, the spinning time was set to 90 min, and the nanofibers were prepared by electrospinning at room temperature. The receiving material of the nanofibers was aluminum foil.

[0060] The aluminum foil receiving the nanofibers was placed in an oven at 80° C. for vacuum drying for 12 h to evaporate the residual N,N-dimethylacetamide solvent in the nanofibers, and then the nanofibers were collected from the aluminum foil.

[0061] (3) Preparation of membrane matrix solution: Add mPBI powder (second polybenzimidazole polymer) into N,N-dimethylacetamide solvent, stir at 80° C. for 12 h until completely dissolved, and prepare a membrane matrix solution with an mPBI concentration of 5 wt %.

[0062] The membrane matrix solution was cooled to room temperature, and then the nanofibers were added to the membrane matrix solution and ultrasonicated for 2 h to disperse the nanofibers in the membrane matrix solution.

[0063] (4) Preparation of proton exchange membrane: adding a crosslinking agent, pyridine-3,5-diyl dimethanol, to the above ultrasonically dispersed solution to obtain a proton exchange membrane slurry. The crosslinking agent accounts for 10% of the total molar fraction of the first polybenzimidazole polymer and the second polybenzimidazole polymer, and the calculation method is as follows:

[0064] The molar fraction of the cross-linking agent=[(the mass of the first polybenzimidazole polymer+the mass of the second polybenzimidazole polymer)÷the molar mass of the repeating unit]×10%.

[0065] The proton exchange membrane slurry was stirred at room temperature for 30 minutes to disperse the crosslinking agent, and then the slurry was coated on a flat glass plate using a doctor blade device with a thickness of 800 μm to 1200 μm. The glass plate was placed in an oven at 80° C. and dried for 24 hours to evaporate the solvent. After drying, the temperature was raised to 160° C. and treated for 1 hour to complete the crosslinking reaction, thereby preparing the nanofiber crosslinked proton exchange membrane of this embodiment.

[0066] In this embodiment, after the proton exchange membrane slurry is coated on the flat glass, the solvent is first evaporated at 80°C, and then cross-linking is completed at 160°C. In other cases, after the slurry is coated on the flat glass, the solvent can be directly evaporated at 140-160°C to complete the cross-linking reaction. However, in this case, the evaporation rate of the solvent is relatively fast, and the evaporation of the solvent in the slurry is uneven, which affects the uniform distribution of the first polybenzimidazole polymer and the second polybenzimidazole polymer in the proton exchange membrane, resulting in an uneven structure of the manufactured proton exchange membrane.

[0067] After the cross-linking reaction is completed, the nanofiber cross-linked proton exchange membrane is immersed in 85 wt % phosphoric acid at 80° C. for 48 hours, and the free phosphoric acid on the membrane surface is wiped dry to obtain a phosphoric acid-doped nanofiber cross-linked proton exchange membrane.

[0068] Example 2

[0069] This embodiment provides a nanofiber cross-linked proton exchange membrane. The difference between the preparation method of the proton exchange membrane and that of Embodiment 1 is that the first polybenzimidazole polymer used in this embodiment is F6-PBI, and the structure is as follows:

[0070]

[0071] Example 3

[0072] This embodiment provides a nanofiber cross-linked proton exchange membrane. The difference between the preparation method of the proton exchange membrane and that of Embodiment 1 is that in this embodiment, the mass ratio of the first polybenzimidazole polymer to the second polybenzimidazole polymer is 1:20.

[0073] Example 4

[0074] This embodiment provides a nanofiber cross-linked proton exchange membrane. The difference between the preparation method of the proton exchange membrane and that of Embodiment 1 is that the first polybenzimidazole polymer and the second polybenzimidazole polymer used in this embodiment are both F6-PBI.

[0075] Figure 1 The graph is a graph showing the proton conductivity of the phosphoric acid-doped nanofiber cross-linked proton exchange membrane prepared in the above embodiments as a function of temperature. The test method is the AC impedance four-electrode method with a scanning frequency of 1-10 6 Hz, tested in a 40-80℃ water bath. Figure 1 As shown, the phosphoric acid-doped nanofiber cross-linked proton exchange membranes prepared in various embodiments of the present invention have relatively high proton conductivity at 140-200° C. Among them, the phosphoric acid-doped nanofiber cross-linked proton exchange membrane prepared in Example 1 has the highest proton conductivity, exceeding 170 mS / cm, which meets the high temperature operating requirements of high-temperature proton exchange membrane fuel cells.

[0076] Figure 2 Figure 2 is a graph showing the mechanical properties of the phosphoric acid-doped nanofiber cross-linked proton exchange membrane prepared in the above-mentioned embodiments. Figure 2 As shown, if the first polybenzimidazole polymer and the second polybenzimidazole polymer are different types of polymers, the phosphoric acid-doped nanofiber cross-linked proton exchange membrane exhibits lower mechanical strength.

[0077] Figure 3 The current-voltage curve of the phosphoric acid-doped nanofiber cross-linked proton exchange membrane prepared in the above embodiments in a single cell. Figure 3 As shown, when the battery voltage decreases, the current density of the battery increases, and at the same battery voltage, the current density of the phosphoric acid-doped nanofiber cross-linked proton exchange membrane prepared in Example 1 is the largest, indicating that the phosphoric acid-doped nanofiber cross-linked proton exchange membrane prepared in Example 1 has the smallest resistance, and the prepared battery has excellent performance.

[0078] In summary, the present invention provides a nanofiber cross-linked proton exchange membrane, which enhances the mechanical strength and proton conductivity of the proton exchange membrane by doping nanofibers prepared by electrospinning into a membrane matrix and cross-linking the nanofibers with the membrane matrix to form a rich network structure.

[0079] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A method for preparing a nanofiber cross-linked proton exchange membrane, characterized in that: include: Step 1, preparation of nanofibers: The first polybenzimidazole polymer is dissolved in a first organic solvent to obtain an electrospinning solution, and then the nanofibers are prepared by an electrospinning process; in the electrospinning solution, the concentration of the first polybenzimidazole polymer is 5wt% to 25wt%; Step 2, preparing membrane matrix solution: Dissolving a second polybenzimidazole polymer in a second organic solvent to obtain a membrane matrix solution; in the membrane matrix solution, the concentration of the second polybenzimidazole polymer is 5wt% to 8wt%; Step 3, preparing a proton exchange membrane: The nanofibers are added to the membrane matrix solution, and after ultrasonic dispersion, a cross-linking agent is added and mixed evenly to form a proton exchange membrane slurry; the cross-linking agent comprises at least one of pyridine-3,5-diyldimethanol, [1,1'-biphenyl]-3,3'-diyldimethanol, 4,4-dichlorobiphenyl, and 4,4'-dichloro-2,2'-bipyridine; The proton exchange membrane slurry is coated on a flat plate and heated to 100° C. to 160° C. to cross-link the first polybenzimidazole polymer and the second polybenzimidazole polymer to form a proton exchange membrane.

2. The method for preparing a nanofiber cross-linked proton exchange membrane according to claim 1, characterized in that: The first polybenzimidazole polymer and the second polybenzimidazole polymer are independently selected from one or more of the following:

3. The method for preparing a nanofiber cross-linked proton exchange membrane according to claim 2, characterized in that: The first polybenzimidazole polymer and the second polybenzimidazole polymer are the same polybenzimidazole polymer.

4. The method for preparing a nanofiber cross-linked proton exchange membrane according to claim 1, characterized in that: In step 1 and step 2, the weight ratio of the first polybenzimidazole polymer to the second polybenzimidazole polymer is 1:3 to 1:

20.

5. The method for preparing a nanofiber cross-linked proton exchange membrane according to claim 1, characterized in that: The first organic solvent and the second organic solvent are independently selected from one or more of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide or dimethyl sulfoxide.

6. The method for preparing a nanofiber cross-linked proton exchange membrane according to claim 1, characterized in that: After step 3, the method further comprises the step of doping with phosphoric acid: At 80° C. to 120° C., the nanofiber cross-linked proton exchange membrane is immersed in 65wt% to 85wt% phosphoric acid to allow phosphoric acid to be doped into the nanofiber cross-linked proton exchange membrane.

7. The method for preparing a nanofiber cross-linked proton exchange membrane according to claim 1, characterized in that: In step 1, the temperature at which the first polybenzimidazole polymer is dissolved in the first organic solvent is 75°C to 85°C; in step 2, the temperature at which the second polybenzimidazole polymer is dissolved in the second organic solvent is 75°C to 85°C; in step 3, the temperature at which the nanofibers are dispersed in the membrane matrix solution is 20°C to 30°C.

8. The method for preparing a nanofiber cross-linked proton exchange membrane according to claim 1, characterized in that: In step 1, the electrospinning voltage is 10 kV to 25 kV, the syringe advancement speed is 0.01 mm / min to 5 mm / min, the spinning distance is 5 cm to 25 cm, and the temperature is 20° C. to 25° C.

9. A nanofiber cross-linked proton exchange membrane, characterized in that: Prepared according to the method according to any one of claims 1 to 8.

10. A high temperature proton exchange membrane fuel cell, characterized in that: Comprising the nanofiber cross-linked proton exchange membrane as claimed in claim 9.